The problem of faith crisis in the drama 'The Bus' by Lukas Bärfuss - E.N. Shevchenko (Ученые записки Казанского университета: Серия Гуманитарные науки)
Lukas Bärfuss, a contemporary Swiss playwright, is one of the brightest representatives of the new German-language drama. L. Bärfuss is interested in the existential problems, such as life and death, love, faith, suffering, and meaning of life. In the center of his dramas, there is always a modern man living in a world that is “bursting at the seams”. This is the world of lost faith and falsified values of classical culture. The play “The Bus” is dedicated to the issues of religion, or rather to the crisis of faith in modern western society. An ordinary story – a bus ride to the mountains – suddenly turns into a journey of the passengers into the depths of their own selves, and ends with their death. The upstart of the plot is the appearance on the bus of a young pilgrim Erica, going to the Polish city of Czestochowa, to appear before the face of the Black Madonna. The presence of the worshiping girl highlights the spiritual emptiness of other passengers. The final apocalyptic picture is in tune with the social pessimism and despair inherent in modern European drama. The purpose of this paper is to analyze the problems of the crisis of faith in modern European society based on the play by Lukas Bärfuss “The Bus”; to study the image of a “lost man”, the one who lost faith in oneself, in goodness and God himself as a new “hero” of modern drama.